A cellular and spatial map of the choroid plexus across brain ventricles and ages - Dani, Neil; Herbst, Rebecca H; McCabe, Cristin; Green, Gilad S; Kaiser, Karol; Head, Joshua P; Cui, Jin; Shipley, Frederick B; Jang, Ahram; Dionne, Danielle; Nguyen, Lan; Rodman, Christopher; et al. (Cell, 2021)
The choroid plexus (ChP) in each brain ventricle produces cerebrospinal fluid (CSF) and forms the blood-CSF barrier. Here, we construct a single-cell and spatial atlas of each ChP in the developing, adult, and aged mouse brain. We delineate diverse cell types, subtypes, cell states, and expression programs in epithelial and mesenchymal cells across ages and ventricles. In the developing ChP, we predict a common progenitor pool for epithelial and neuronal cells, validated by lineage tracing. Epithelial and fibroblast cells show regionalized expression by ventricle, starting at embryonic stages and persisting with age, with a dramatic transcriptional shift with maturation, and a smaller shift in each aged cell type. With aging, epithelial cells upregulate host-defense programs, and resident macrophages upregulate interleukin-1β (IL-1β) signaling genes. Our atlas reveals cellular diversity, architecture and signaling across ventricles during development, maturation, and aging of the ChP-brain barrier.
Keywords: buněčná diferenciace; mozek; Age Factors; Aging; myši; Mice, Inbred C57BL; mužské pohlaví; Signal Transduction; Male; Cell Differentiation; Cell Lineage; Choroid Plexus; Female; plexus chorioideus; Blood-Brain Barrier; Brain; analýza jednotlivých buněk; Brain Diseases; ženské pohlaví; Epithelial Cells; myši inbrední C57BL; signální transdukce; buněčný rodokmen; Animals; hematoencefalická bariéra; epitelové buňky; Single-Cell Analysis; Mice; zvířata; stárnutí; nemoci mozku; věkové faktory